Prediksi Retensi Customer Berdasarkan Support Vector Machine dengan Preprocessing Menggunakan Hadoop - Giovanni Gabriela Gunadi; Silvia Rostianingsih; Andre Gunawan (Jurnal Infra, 2020)
Nowadays, many companies often offer a discount to customer. The goal is that the company can attract new customers. However, the offer given cannot be done randomly. Offers must be directed to the right customers so the company doesn’t need to spend much money. This study will analyze to determine whether there is an influence of the association rule on customer retention. The data used is the Acquire Valued Shopper Challenge taken from the Kaggle website. As the program used is java with the Hadoop framework that uses the association rule method. Tests carried out twice using different data. The objective to be achieved from testing is that the model created can predict customers who will retain if they get an offer. With the tests carried out, the best results to answer the objective is to use data in the second experiment with the ratio of training data to testing data is 7: 3 and gamma 0.1 with accuracy obtained is 58.21%.